Assessment of whole-body vibration in hydraulic rock breaker operators based on operating parameters - P. Vikram; Mangalpady Aruna; Abhishek Kumar Tripathi; Syed Ariff; Aschalew Cherie (Discover Applied Sciences)
Abstract The study evaluates the impact of whole-body vibration (WBV) on rockbreaker operators in Indian mechanized quarries. The study was performed on three different operating parameters scenario with varied power and rate such as Operating parameter-(1) Impact power 37.25 HP with impact rate of 420–450 blows/min, Operating parameter-(2) Impact power 43 HP with Impact rate of 350–375 blows/min and operating parameter-(3) Impact power equal to 54 HP with impact rate of 280–300 blows/min. WBV data was collected from five rockbreaker operators using a seat pad tri-axial accelerometer, across three different operating parameters. The results indicated that all the rockbreaker operators exceeded the A(8) based exposure action value (EAV) of 0.5 m/s2 in all the three operating parameters but all the rockbreaker operators in the third operating parameter have exceeded the A (8)-based exposure limit value (ELV) of 1.15 m/s2 and vibration dose value (VDV) based exposure limit value (EAV) of 9.1 m/s1.75. The study’s findings suggest that the vibration amplification for operators working in operating parameter-1 was reduced completely compared to those working in the second and third operating parameters, based on the above “Health Guidance Caution Zone (HGCZ)” for daily vibration exposure, specifically A (8) and VDV (8) measurements, Based on the aforementioned observation, it can be inferred that operating parameter-1 is an advantageous setting, as it minimizes the vibration experienced by the rockbreaker operators.